Trypanosoma cruzi surface mucins are involved in the attachment to the Triatoma infestans rectal ampoule - Camara, Maria de Los Milagros (2019)
Chagas disease, caused by the protozoan Trypanosoma cruzi, is a life-long and debilitating neglected illness of major significance to Latin America public health, for which no vaccine or adequate drugs are yet available. In this scenario, identification of novel drug targets and/or strategies aimed at controlling parasite transmission are urgently needed. By using ex vivo binding assays together with different biochemical and genetic approaches,we herein show that Gp35/50 kDa mucins, the major T. cruzi epimastigote surface glycoproteins, specifically adhere to the internal cuticle of the rectal ampoule of the triatomine vector, a critical step leading to their differentiation into mammal-infective metacyclic forms. Ex vivo binding assays in the presence of chemically synthesized analogs allowed the identification of a solvent-exposed peptide and a branched, galactofuranose (Galf)-containing trisaccharide (Galfβ1-4[Galpβ1-6]GlcNAcα) as major Gp35/50 kDa mucins adhesion determinants. Overall, these results provide novel insights into the mechanisms underlying the complex T. cruzi-triatomine interplay. In addition, and since the presence of Galf-based glycotopes on the O-glycans of Gp35/50 kDa mucins is restricted to certain parasite strains/clones, they also indicate that the Galfβ1?4[Galpβ1?6]GlcNAcα motif may contribute to the well-established phenotypic variability among T. cruzi isolates. Most importantly, and taking into account that Galf residues are not found in mammals, we propose Gp35/50 kDa mucins and/or Galf biosynthesis as appealing and novel targets for the development of T. cruzi transmission-blocking strategies.